Pressure-induced structural stability of alkali trihydrides and H2-desorption occurrence: Ab initio study for hydrogen storage improvement - Prayoonsak Pluengphon (2020)
© 2020 Hydrogen Energy Publications LLC Alkali trihydrides in the forms of LiH(H2) and NaH(H2) have attracted considerable attention due to its containing of the high-gravimetric hydrogen capacity. Structural and mechanical stabilities, thermodynamic and electronic properties, and H-vacancy occurrences of the alkali trihydrides at high pressures 40–70 GPa are analyzed using ab initio calculation. Phonon stability of LiH(H2) has been predicted at pressure above 40 GPa, while the stability of NaH(H2) at 50 GPa confirms the discovery of previous experiment. Born stability criteria indicates the mechanical stability of LiH(H2) and NaH(H2) in the Cmcm phase. Heat capacity and H-vacancy enthalpy of the alkali trihydrides decrease with an increasing of pressure, indicating the hydrogen storage improvement. The diffusion kinetics and translation paths of H− and H2 vacancies are also investigated. These indicate that the LiH(H2) requires lower energy exchange for hydrogen desorption compared to the NaH(H2).